AAV-based vectors for human diseases modeling in laboratory animals - Aliev, Timur I.; Yudkin, Dmitry V. (Frontiers in Medicine, 2025)
The development of therapeutic drugs and vaccines requires the availability of appropriate model animals that replicate the pathogenesis of human diseases. Both native and transgenic animals can be utilized as models. The advantage of transgenic animals lies in their ability to simulate specific properties desired by researchers. However, there is often a need for the rapid production of transgenic animal models, especially in situations like a pandemic, as was evident during COVID-19. An important tool for transgenesis is the adeno-associated virus. The genome of adeno-associated virus serves as a convenient expression cassette for delivering various DNA constructs into cells, and this method has proven effective in practice. This review analyzes the features of the adeno-associated virus genome that make it an advantageous vector for transgenesis. Additionally, examples of utilizing adeno-associated viral vectors to create animal models for hereditary, oncological, and viral human diseases are provided.